An Update on AMPK in Hydrogen Sulfide Pharmacology - Wang, Minjun; Tang, Wenbo; Zhu, Yi Zhun (Frontiers in Pharmacology, 2017)
Hydrogen sulfide (H2S), the third bio-active gasotransmitter, is produced endogenously and tightly involved in the pathogenesis and treatment for various diseases. Adenosine 5’-monophosphate-activated protein kinase (AMPK) plays a paramount role in maintaining cellular energetic balance. Increasing evidences have also suggested AMPK as a novel modulator in multiple pathological conditions. In this paper, we will review the biological principles of H2S and AMPK, and most importantly, the recent discoveries regarding AMPK-mediated pharmacological actions of H2S. Emphasis will be laid on AMPK/H2S interactions in the cardiovascular system, autophagy, diabetic complications, and inflammation. In most cases described in this article, by promoting AMPK activation, H2S exerts cytoprotective effects or therapeutic potentials, though there remain some controversies before we can fully understand the involved mechanisms. Further researches are in need to investigate more closely any relationship between H2S and AMPK, and to put forward the development of H2S donors for clinical application.